Randomized Trial: Quitline Specialist Training in Gain-Framed vs Standard-Care Messages for Smoking Cessation - Toll, Benjamin A. (Oxford University Press, 2010)
BACKGROUND: Smoking accounts for a large proportion of cancer-related mortality, creating a need for better smoking cessation efforts. We investigated whether gain-framed messages (ie, presenting benefits of quitting) will be a more persuasive method to encourage smoking cessation than standard-care messages (ie, presenting both costs of smoking [loss-framed] and benefits of quitting). METHODS: Twenty-eight specialists working at the New York State Smokers’ Quitline (a free telephone-based smoking cessation service) were randomly assigned to provide gain-framed or standard-care counseling and print materials. Smokers (n = 2032) who called the New York State Smokers’ Quitline between March 10, 2008, and June 13, 2008, were exposed to either gain-framed (n = 810) or standard-care (n = 1222) messages, and all medically eligible callers received nicotine replacement therapy. A subset of 400 call recordings was coded to assess treatment fidelity. All treated smokers were contacted for 2-week and 3-month follow-up interviews. All statistical tests were two-sided. RESULTS: Specialists providing gain-framed counseling used gain-framed statements statistically significantly more frequently than those providing standard-care counseling as assessed with frequency ratings for the two types of gain-framed statements, achieving benefits and avoiding negative consequences (for achieving benefits, gain-framed mean frequency rating = 3.9 vs standard-care mean frequency rating = 1.4; mean difference = −2.5; 95% confidence interval [CI] = −2.8 to −2.3; P < .001; for avoiding negative consequences, gain-framed mean frequency rating = 1.5 vs standard-card mean frequency rating = 1.0; mean difference = −0.5; 95% CI = −0.6 to −0.3; P < .001). Gain-framed counseling was associated with a statistically significantly higher rate of abstinence at the 2-week follow-up (ie, 99 [23.3%] of the 424 in the gain-framed group vs 76 [12.6%] of the 603 in the standard-care group, P < .001) but not at the 3-month follow-up (ie, 148 [28.4%] of the 522 in the gain-framed group vs 202 [26.6%] of the 760 in the standard-care group, P = .48). CONCLUSIONS: Quitline specialists can be trained to provide gain-framed counseling with good fidelity. Also, gain-framed messages appear to be somewhat more persuasive than standard-care messages in promoting early success in smoking cessation.